1987
DOI: 10.1088/0022-3727/20/6/010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the arc velocity on the cathode erosion rate in argon-nitrogen mixtures

Abstract: Erosion measurements on a copper cathode are reported. The 100 A arc, driven by a magnetic field, runs continuously for up to 30 min between two concentric cylindrical electrodes. Argon-nitrogen gas mixtures in various proportions are blown through the electrode gap. The erosion rate in argon is drastically reduced by the addition of only 1% nitrogen and is further reduced as the nitrogen content increases in the gas mixtures. The decrease in erosion rate is found to be correlated to an increase in arc velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 7 publications
2
27
0
5
Order By: Relevance
“…With an effective enthalpy of h ef = 130 MJkg −1 , we obtained in Fig. 1b a rather good agreement of the continuous model to the experimental data 11. The difference between these g 0 and h ef values and those presented in this paper may be explained by the difference in the plasma gas composition and in the material of electrodes 11.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…With an effective enthalpy of h ef = 130 MJkg −1 , we obtained in Fig. 1b a rather good agreement of the continuous model to the experimental data 11. The difference between these g 0 and h ef values and those presented in this paper may be explained by the difference in the plasma gas composition and in the material of electrodes 11.…”
Section: Resultssupporting
confidence: 76%
“…1b a rather good agreement of the continuous model to the experimental data 11. The difference between these g 0 and h ef values and those presented in this paper may be explained by the difference in the plasma gas composition and in the material of electrodes 11. The authors in 11 used pure electrolytic copper as cathode material and argon‐nitrogen mixtures as the plasma‐forming gas.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…For a given current, the velocity of the attachment movement is the principal factor determining cathode erosion. Szente et al [1987a, 1987b] found for a magnetically driven 100A arc between two concentric tubular copper electrodes a relationship for the velocity dependence of the erosion rate…”
Section: Cold Cathodesmentioning
confidence: 99%